Conditioned CAR-T cells by hypoxia-inducible transcription amplification (HiTA) system significantly enhances systemic safety and retains antitumor efficacy - Xiaoyan Zhang; Huan He; Chen Zhao; Min Yuan; Xiangqing Ding; Qibin Liao; Jianqing Xu; Cuisong Zhu; Meiqi Feng; Zhuoqun Liu; Lang Jiang; Linxia Zhang (Journal for ImmunoTherapy of Cancer)
Background Hypoxia is a striking feature of most solid tumors and could be used to discriminate tumors from normoxic tissues. Therefore, the design of hypoxia-conditioned Chimeric Antigen Receptor (CAR) T cells is a promising strategy to reduce on-target off-tumor toxicity in adoptive cell therapy. However, existing hypoxia-conditioned CAR-T designs have been only partially successful in enhancing safety profile but accompanied with reduced cytotoxic efficacy. Our goal is to further improve safety profile with retained excellent antitumor efficacy.Methods In this study, we designed and constructed a hypoxia-inducible transcription amplification system (HiTA-system) to control the expression of CAR in T (HiTA-CAR-T) cells. CAR expression was determined by Flow cytometry, and the activation and cytotoxicity of HiTA-CAR-T cells in vitro were evaluated in response to antigenic stimulations under hypoxic or normoxic conditions. The safety of HiTA-CAR-T cells was profiled in a mouse model for its on-target toxicity to normal liver and other tissues, and antitumor efficacy in vivo was monitored in murine xenograft models.Results Our results showed that HiTA-CAR-T cells are highly restricted to hypoxia for their CAR expression, activation and cytotoxicity to tumor cells in vitro. In a mouse model in vivo, HiTA-CAR-T cells targeting Her2 antigen showed undetectable CAR expression in all different normoxic tissues including human Her2-expresing liver, accordingly, no liver and systemic toxicity were observed; In contrast, regular CAR-T cells targeting Her2 displayed significant toxicity on human Her2-expression liver. Importantly, HiTA-CAR-T cells were able to achieve signiﬁcant tumor suppression in murine xenograft models.Conclusion Our HiTA system showed a remarkable improvement in hypoxia-restricted transgene expression in comparison with currently available systems. HiTA-CAR-T cells presented significant antitumor activities in absence of any significant liver or systemic toxicity in vivo. This approach could be also applied to design CAR-T cell targeting other tumor antigens.